1992
DOI: 10.1111/j.1365-2621.1992.tb08075.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality Attributes of Strawberry Cultivars Grown in British Columbia

Abstract: Strawberries from six cultivars, 'Mrak', 'Ranier', 'Redcrest', 'Selva', 'Sumas' and 'Totem', were compared for sensory attributes, chemical properties and 25 selected volatile compounds. 'Redcrest' strawberries had the most intense sourness, lowest pH, high titratable acidity and least overall fruit quality rating. Two-dimensional partitioning (TDP) revealed that overall quality ratings of the strawberries from all cultivars were dependent primarily on odor and sweetness. Cultivars differed in all orthogonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 16 publications
1
15
0
1
Order By: Relevance
“…Sensory attributes are important aspects of fruit quality. Sensory attributes, such as color, texture, odor and the balance between sweetness and sourness have been identified as important determinants of overall quality of fruits such as strawberry (Shamaila et al 1992). Results of sensory analysis for the two cherry varieties are shown in Table 3.…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…Sensory attributes are important aspects of fruit quality. Sensory attributes, such as color, texture, odor and the balance between sweetness and sourness have been identified as important determinants of overall quality of fruits such as strawberry (Shamaila et al 1992). Results of sensory analysis for the two cherry varieties are shown in Table 3.…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…Woodward (1972) reported that strawberry fruits had an initial phase of growth and enlargement followed by a maturation phase. Firmness, color, and the sugar/acid ratio are important determinants of overall quality in ripe strawberry fruits (Shamaila et al, 1992). The loss of firmness during the ripening is a major factor determining the strawberry fruit quality and postharvest shelf-life.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the relationship between carbohydrates and sensory attributes, such as fruit sweetness, has been thoroughly studied. [33][34][35] In our experiments, SS, TA, SS:TA ratio, pH value, total solids (TS) and anthocyanin content were examined in four strawberry cultivars obtained from two types of cultivation. The corresponding data are shown in Table 3.…”
Section: Descriptive and Physicochemical Sensory Analysismentioning
confidence: 99%